1993
DOI: 10.1128/jb.175.7.1929-1935.1993
|View full text |Cite
|
Sign up to set email alerts
|

The sigma B-dependent promoter of the Bacillus subtilis sigB operon is induced by heat shock

Abstract: oE, a secondary sigma factor of Bacillus subtilis, was found to increase 5-to 10-fold when cultures were shifted from 37 to 48°C. Western blot (immunoblot) analyses, in which monoclonal antibodies specific for the sigB operon products RsbV, RsbW, and crB were used to probe extracts from wild-type and mutant B. subtilis strains, revealed that all three proteins increased coordinately after heat shock and that this increase was dependent on &rB but not RsbV, a positive regulator normally essential for &3-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
118
2
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 28 publications
2
118
2
1
Order By: Relevance
“…The transcription factor B of B. subtilis controls a set of genes that are induced both upon entry into stationary phase and by a variety of physiological stresses encountered during logarithmic growth (4,6,7,9,25,29,51). Previous genetic analysis indicated that the products of the rsbV, rsbW, and rsbX genes in the sigB operon form a hierarchical regulatory pathway that controls B activity in response to stationary-phase signals as well as to signals of salt and ethanol stress (2,6,8,24,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor B of B. subtilis controls a set of genes that are induced both upon entry into stationary phase and by a variety of physiological stresses encountered during logarithmic growth (4,6,7,9,25,29,51). Previous genetic analysis indicated that the products of the rsbV, rsbW, and rsbX genes in the sigB operon form a hierarchical regulatory pathway that controls B activity in response to stationary-phase signals as well as to signals of salt and ethanol stress (2,6,8,24,29).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, recent work has shown that B is also activated in logarithmically growing cells by a variety of environmental stresses that limit growth, including hyperosmosis, heat, oxidative stress, and ethanol shock (4,6,51). These findings have led to the proposal that B controls a general stress regulon (6).…”
mentioning
confidence: 99%
“…There is a growing list of conditions, including entry into stationary phase, heat shock, osmotic shock, ethanol treatment, and anaerobiosis, etc., which lead to activation of B (2,4,7,9,16,26). In each instance, activation of B presumably involves its release from RsbW.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of heat shock activation, all known B activation processes require RsbV (2,3,4,7,9). Therefore, we wished to test whether the RsbU-dependent activation that occurs in the absence of RsbX also requires RsbV or whether it defines a novel B activation system.…”
Section: Vol 177 1995 Rsbu Regulation Of B 117mentioning
confidence: 99%
See 1 more Smart Citation